HUBUNGAN ANTARA KONSUMSI GULA BERLEBIH DENGAN KEJADIAN ACNE VULGARIS PADA SISWA LAKI-LAKI SMA PERTIWI 1 PADANG - Yola Sherina; Prima Minerva (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Acne vulgaris is a skin disease caused by the accumulation of excess oil that clogs the pores of the facial skin, triggering bacterial growth and inflammation of the skin. One of the factors contributing to the occurrence of acne vulgaris is diet, particularly excessive sugar consumption. This study aims to determine the relationship between excessive sugar consumption and the incidence of acne vulgaris in male students at SMA Pertiwi 1 Padang. This research is a quantitative study with a correlational analytic method and a cross-sectional design. The population of this study consists of 90 male students at SMA Pertiwi 1 Padang who have acne vulgaris, and a sample of 47 students was obtained using consecutive sampling techniques. Data were collected using the Food Frequency Questionnaire (FFQ) and analysed using the Chi-Square test. The results showed that most respondents experienced mild acne vulgaris, with 23 individuals (48.9%), while the majority had a high sugar intake (50 grams per day), consisting of 24 individuals (51.1%). The Chi-Square test results indicated a significant relationship between excessive sugar consumption and the incidence of acne vulgaris (p = 0.001; p 0.05). The conclusion of this study is that there is a significant relationship between excessive sugar consumption and the incidence of acne vulgaris among male students at SMA Pertiwi 1 Padang. It is expected that students will pay more attention to their daily sugar intake and reduce the consumption of sweet foods and drinks to prevent the occurrence of acne vulgaris. Keywords: Excessive Sugar Consumption, Acne Vulgaris